If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 9 = 8x + 8 Reorder the terms: 9 + 7x = 8x + 8 Reorder the terms: 9 + 7x = 8 + 8x Solving 9 + 7x = 8 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 9 + 7x + -8x = 8 + 8x + -8x Combine like terms: 7x + -8x = -1x 9 + -1x = 8 + 8x + -8x Combine like terms: 8x + -8x = 0 9 + -1x = 8 + 0 9 + -1x = 8 Add '-9' to each side of the equation. 9 + -9 + -1x = 8 + -9 Combine like terms: 9 + -9 = 0 0 + -1x = 8 + -9 -1x = 8 + -9 Combine like terms: 8 + -9 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1
| -3+2=13y-5-12y | | 4x+3x=30+9 | | m/2+5=--3 | | 6(3m-3)=34+5m | | 3x+8=22+x | | 2(1)(6(4)-5)= | | 125*5(3x)=27*27(x) | | 0.35(2y-1)=-0.7y | | d+7=-7 | | y-34+12+3=14 | | 2x+24=.29x | | (x+10)(2x)(2x-30)= | | -2(-3k+4)-7=15 | | -3(x-4)=2(x+1) | | 22.5x-15=12 | | 4n-6=8+2n | | 9=7-2c | | 125*5(3x)=27*27x | | 8x+7=4x+47 | | x+10-18=-5 | | 45+35x=20+40x | | y=2mx+7b | | 2(3x+1)-3(-4x+1)=20x-19 | | X+17=12-19 | | 4x^2+5=2y | | -16=x+(-22) | | 4n-5=-17 | | -8(5n+7)=40-8n | | 4x-6+42=90 | | 2[d-(4d+13)+3]=2(d+10) | | 22.5x-15.0=12 | | 2y(6z-x)= |